Biomechanical parameters of gait among transtibial amputees: a review - Soares, Alex Sandra Oliveira de Cerqueira (2019)
Made available in DSpace on 2019-09-12T16:25:51Z (GMT). No. of bitstreams: 0 Previous issue date: 2009